Cognitive performance in patients with chronic schizophrenia across the lifespan - Herold, Christina; Schmid, Lena A.; Schröder, Johannes (GeroPsych, 2017)
Chronic schizophrenia involves neuropsychological deficits that primarily strike executive functions and episodic memory. Our study investigated these deficits throughout the lifespan in patients with chronic schizophrenia and in healthy controls. Important neuropsychological functions were tested in 94 patients and 66 healthy controls, who were assigned to three age groups. Compared with the healthy controls, patients performed significantly poorer on all tests applied. Significant age effects occurred on all tests except the digit span forward, with older subjects scoring well below the younger ones. With respect to cognitive flexibility, age effects were more pronounced in the patients. These findings underline the importance of cognitive deficits in chronic schizophrenia and indicate that diminished cognitive flexibility shows age-associated differences.